2022
DOI: 10.1094/pdis-06-21-1151-re
|View full text |Cite
|
Sign up to set email alerts
|

Alternaria spp. Associated with Leaf Blight of Maize in Heilongjiang Province, China

Abstract: Maize is a major economic crop worldwide. Maize can be infected by Alternaria species causing leaf blight that can result in significant economic losses. In this study, 168 Alternaria isolates recovered from symptomatic maize leaves were identified based on morphological characteristics, pathogenicity, and multi-locus sequence analyses of glyceraldehyde-3-phosphate dehydrogenase (GAPDH), the internal transcribed spacer of ribosomal DNA (rDNA ITS), the RNA polymerase II second largest subunit (RPB2), and histon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 78 publications
0
14
0
Order By: Relevance
“…Furthermore, C. papendorfii (synonym: B. papendorfii) was shown to be a pathogen of maize in China [46]. Alternaria species including A. tenuissima, A. alternata, and A. burnsii were shown to cause disease in maize [47,48]. Migration of these pathogenic fungal species to maize may have happened from adjacent sugarcane or rice fields or due to secondary inoculum developed on previous crops in the rotation schedule, which necessitates further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, C. papendorfii (synonym: B. papendorfii) was shown to be a pathogen of maize in China [46]. Alternaria species including A. tenuissima, A. alternata, and A. burnsii were shown to cause disease in maize [47,48]. Migration of these pathogenic fungal species to maize may have happened from adjacent sugarcane or rice fields or due to secondary inoculum developed on previous crops in the rotation schedule, which necessitates further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Paramyrothecium abundances were significantly lower in CFM than in other treatments. Furthermore, Alternaria, which can cause potato brown spot and potato early blight, was most abundant in CK and CF (Xu et al, 2022). Cladosporium is a saprophytic taxon but is also an important plant pathogen that mainly infects plant leaves, branches, and fruits, resulting in poor quality and reduced yields (Bensch et al, 2012).…”
Section: Effects Of Long-term Fertilization On Composition Of Microbi...mentioning
confidence: 99%
“…The results obtained revealed that Alternaria alternata KSU4M1-1 caused dramatic losses of seedling survival (67%) as compared with the control treatment (96%). Recently, A. alternata was reported to be among four causal agents of Alternaria leaf spot disease on maize seedlings [ 50 ]. Other studies have stated that the risk is not only due to the yield loss they cause but also due to reduction in the grain quality (discoloration) and nutritive value, in addition to an array of Alternaria mycotoxins that belong to three derivatives: tetramic acid, dibenzopyrone, and perylene, which play an important role in the pathogenesis and can inhibit the germination of maize as well [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%